Multidimensional Model of Distance Learning Environment - Katane, Irēna; Katans, Edgars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Education diversification is a precondition for the sustainability of the society and education as such. Diversified education can ensure the accessibility of education, as well as individualization according to the needs of the society. Distance learning is one of education alternatives. Research in the field of distance learning environment shall be based on the ecological approach in education, which has many and various forms. Multidimensional approach is one of them. The aim of the article is to justify the multidimensional model of distance learning environment, that comprises: 1) self-directed learning pedagogical support environment; 2) informative environment; 3) technological environment; 4) e-environment. The multidimensional approach promotes holistic approach, thus avoiding unilateralism in relation to research in the distance learning environment specificity, as well as to its development.